2014
DOI: 10.1021/ja502749f
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Fibril Disruption by Ultrasonic Cavitation: Nonequilibrium Molecular Dynamics Simulations

Abstract: We describe the disruption of amyloid fibrils of Alzheimer's amyloid-β peptides by ultrasonic cavitation. For this purpose, we performed nonequilibrium all-atom molecular dynamics simulations with sinusoidal pressure and visualized the process with movies. When the pressure is negative, a bubble is formed, usually at hydrophobic residues in the transmembrane region. Most β-strands maintain their secondary structures in the bubble. When the pressure becomes positive, the bubble collapses, and water molecules cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 35 publications
2
89
1
Order By: Relevance
“…)404142 was used to perform the MD simulations. The AMBER parm99SB force field43 was used for the TRP channel and the general AMBER force field was used for HC39.…”
Section: Methodsmentioning
confidence: 99%
“…)404142 was used to perform the MD simulations. The AMBER parm99SB force field43 was used for the TRP channel and the general AMBER force field was used for HC39.…”
Section: Methodsmentioning
confidence: 99%
“…Despite great progress achieved in the field, the exact role of Aβ is still not well understood. 6 Numerous therapeutic approaches (such as use of Aβ-degrading enzymes, 7 the ultrasound technique, 8,9 mid-infrared free-electron laser technology, 10 etc.) that target the production, toxicity and removal of Aβ have been developed during the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Several MD simulation studies have revealed the aggregation131415161718192021222324 and disaggregation252627 of A β amyloid fibrils, and a few MD studies have reported easy deformation of the A β molecules at the two fibril ends under high temperature (398 K) conditions2829. However, the structural and fluctuational differences between the odd and even ends have not been investigated.…”
mentioning
confidence: 99%